Simultaneous resection of a gastric submucosal lipoma in the setting of bariatric surgery: A case report and review of current literature. (2019) - Agafonoff, Slava; Pitt, Tracy; Max, Joshua; Udelhofen, Steven; Braverman, Timothy S.; Lenobel, Robert S.
Highlights: Important to rule out other tumors, such as GIST and malignancy. Pre-operative imaging including EUS is critical in choosing the appropriate surgery. Multiple modalities exist for excision of lipoma in setting of bariatric surgery. Abstract: Introduction: Gastric submucosal lipoma is an uncommon finding in the stomach. A benign fatty tumor that is asymptomatic majority of the time. However, symptomatic and bigger tumors can be difficult to manage surgically and require detailed surgical planning prior to proceeding with bariatric surgery. Presentation of case: 58 year old female who presented for weight loss consultation. Underwent an esophagogastroduodenoscopy (EGD) that demonstrated a 3 cm mass near the incisura. Endoscopic ultrasound (EUS) and biopsy demonstrated a submucosal lipoma. Due to the lipoma's location, resection was critical, as it would have led to obstructive symptoms following sleeve gastrectomy. The patient underwent a simultaneous laparoscopic vertical gastrectomy, gastric lipoma excision, EGD, and laparoscopic cholecystectomy Discussion: Gastric lipomas are benign gastric submucosal tumors, representing less than 3% of all benign gastric neoplasms. Computer tomography and endoscopic ultrasound are important in establishing diagnosis. In current literature, excision with negative margins is standard of care, but small asymptomatic lesions can be followed without intervention. Conclusion: Gastric lipoma are a rare type of gastric submucosal tumors. Size is highly variable. Observation is a reasonable approach when small and asymptomatic, but multiple surgical modalities can be utilized to remove the tumor. Careful utilization of pre-operative imaging including EUS is critical in choosing the appropriate surgery if simultaneous bariatric management is undertaken